The Realignment of Poqo as the PAC: A Remedial to South Africa's Apartheid and Post-Apartheid Liberation Historiography - Dlanga, Thand'Olwethu (African historical review, 2023)
Post-apartheid South Africa's liberation historiography has been constructed and curated in a manner that influences public and collective memory to assume that only one specific liberation movement (the African National Congress) was involved in the South African liberation struggle. The Pan Africanist Congress (PAC) and its military wing, the Azanian People's Liberation Army (APLA), have largely been given perfunctory attention or ignored because of bias and the selective politics of memory. In instances where the history of PAC or APLA is given some attention pre and post-apartheid, the focus has been mainly on uPoqo as the paramilitary wing of the PAC, or on the leadership conflicts within it, at the expense of interrogating other important aspects within the movement. This article explores the development of the term Poqo, mapping its roots from the shorthand for "Umbutho wama-Afrika Poqo." It then shows that the prohibition of the PAC in 1960 after the Sharpeville massacre led the movement to operate under the auspices of Poqo, an underground name. Furthermore, this article demonstrates that Poqo was not a paramilitary wing of the PAC but is/was the PAC itself in another form. Ultimately, this historical and historiographical contribution seeks to achieve a re-alignment of Poqo in South Africa's post-apartheid history writing and public memory.